Antagonistic functions of LMNA isoforms in energy expenditure and lifespan. (17th March 2014) - Lopez‐Mejia, Isabel C; de Toledo, Marion; Chavey, Carine; Lapasset, Laure; Cavelier, Patricia; Lopez‐Herrera, Celia; Chebli, Karim; Fort, Philippe; Beranger, Guillaume; Fajas, Lluis; Amri, Ez Z; Casas, François; et al.
Synopsis <boxed-text content-type="graphic" id="embr201338126-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> The LMNA gene encodes functionally distinct isoforms that have opposite effects on energy metabolism and lifespan. Mice expressing lamin C only are obese and have an extended lifespan, whereas mice expressing progerin are lean and die early. Mice exclusively expressing the lamin C isoform exhibit decreased energy metabolism and mitochondrial activity. Exclusive lamin C expression in mice results in an increased lifespan and weight gain. Progerin‐expressing mice present a higher energy metabolism and are lipodystrophic. Key modulators of energy expenditure are inversely regulated in lamin C‐ and progerin‐expressing mice.